1999
DOI: 10.1063/1.123562
|View full text |Cite
|
Sign up to set email alerts
|

A monohydride high-index silicon surface: Si(114):H-(2×1)

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It has been shown that Si(114) could be successfully hydrogenated with a well-ordered, low-defect-density monohydrate at about 400°C during atomic hydrogen exposure. 16 A similar study was performed on the interaction of atomic hydrogen with a reconstructed nanofaceted Si(211) surface. 17 Molecular-beam epitaxy (MBE) of HgCdTe infrared detector structures for two-color thermal imaging system requires (211) substrate orientation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Si(114) could be successfully hydrogenated with a well-ordered, low-defect-density monohydrate at about 400°C during atomic hydrogen exposure. 16 A similar study was performed on the interaction of atomic hydrogen with a reconstructed nanofaceted Si(211) surface. 17 Molecular-beam epitaxy (MBE) of HgCdTe infrared detector structures for two-color thermal imaging system requires (211) substrate orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the Si(1 1 4) surface is known to have the simplest and single-domain structure composed of dimer (D), rebonded atom (R), and tetramer (T) rows [22][23][24]. Until now, several adsorption studies on Si(1 1 4) have been performed: hydrogen passivation for enhancing the potential of Si(1 1 4) as a substrate for homoepitaxy [25,26], the dissociative chemisorption of Cl 2 as a template for patterning via halogen-etching [27], and C 2 H 4 chemisorption for the development of methods to incorporate functional organic nanostructures onto semiconductor substrates for electronic and optoelectronic device applications [28]. But, the previous C 2 H 4 chemisorption study on Si(1 1 4) is limited to adsorption at room temperature (RT), which is not enough to achieve saturated C incorporation obtained at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although more complex than Si(001)-(2×1), 8,9 the clean Si(114) surface reconstruction includes only two additional structural elements in addition to the dimer row. Moreover, the surface can be monohydride terminated with little change in the surface structure, 10 suggesting that ordered chemisorbed monolayers might be possible despite the presence of multiple potential chemisorption geometries. As displayed in Figure 1, the Si(114)-(2×1) surface consists of periodic rows of rebonded (001)-like "B-type" double-layer steps, tetramers, and (001)-like dimers.…”
Section: Introductionmentioning
confidence: 99%